Assessment of Femoral Head Coverage in Healthy Children Younger than 6 Years Old - Suvorov Vasyl; Filipchuk Viktor; Zyablovskyi Evhen (Research Developments in Medicine and Medical Science Vol. 2, 2023)
This chapter aims to assess the femoral head coverage in healthy children younger than 6 years. This study included 270 hip joint CTscans, and digital pelvic models were created according to these scans. FH coverage by the five acetabular regions was assessed according to patient’s age and sex. It was found that the growth process of different acetabular regions occurs nonlinearly with the periods of acceleration. Examining sex variations in the FH coverage, it was discovered that male children had more extensive superior-anterior covering while female children had posterior coverage.